(untitled) (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1984-86) Editor-in-Chief - GOPAL SWARUP, Nematology Divn., LA.R.I., New Delhi Editor - D.R. DASGUPTA, Nematology Divn., LA.R.I., New Delhi Members - P.K. KOSHY, Kayangulam - Y.S. RAo, Cuttack - B.S. YAPAV, Udaipur - S.K. SAXENA, Aligarh